The Impact of Smoking on Microbiota: A Narrative Review - Sara Cicchinelli; Federico Rosa; Federica Manca; Christian Zanza; Veronica Ojetti; Marcello Covino; Marcello Candelli; Antonio Gasbarrini; Francesco Franceschi; Andrea Piccioni (2023)
Cigarette smoke is a classic risk factor for many diseases. The microbiota has been recently indicated as a new, major player in human health. Its deregulation-dysbiosis-is considered a new risk factor for several illnesses. Some studies highlight a cross-interaction between these two risk factors-smoke and dysbiosis-that may explain the pathogenesis of some diseases. We searched the keywords "smoking OR smoke AND microbiota" in the title of articles on PubMed®, UptoDate®, and Cochrane®. We included articles published in English over the last 25 years. We collected approximately 70 articles, grouped into four topics: oral cavity, airways, gut, and other organs. Smoke may impair microbiota homeostasis through the same harmful mechanisms exerted on the host cells. Surprisingly, dysbiosis and its consequences affect not only those organs that are in direct contact with the smoke, such as the oral cavity or the airways, but also involve distant organs, such as the gut, heart, vessels, and genitourinary tract. These observations yield a deeper insight into the mechanisms implicated in the pathogenesis of smoke-related diseases, suggesting a role of dysbiosis. We speculate that modulation of the microbiota may help prevent and treat some of these illnesses.